The Role of Dynamic Renal Scintigraphy in Detecting Vesicoureteral Reflux Diagnosed by Voiding Cystourethrogram - İlhan Çiftci; Gonca Kara Gedik; Farise Yılmaz; Fatma Özcan Sıkı; Hasan Önner; Mehmet Sarıkaya (Genel Tıp Dergisi)
Aims: This study aims to evaluate the role of standardized dynamic renal scintigraphy (DRS) in recognizing vesicoureteral reflux (VUR) in patients detected with VUR by voiding cystourethrography (VCUG). Methods: The data of all pediatric patients who underwent both VCUG and DRS [technetium-99m diethylenetriamine pentaacetic acid (Tc-99m DTPA) or technetium-99m mercaptoacetyltriglycine dynamic renal scintigraphy (Tc-99m MAG-3)] in our hospital between 2013 and 2022 were retrospectively reviewed. Tc-99m MAG-3 was used in infants and Tc-99m DTPA radiopharmaceutical in children over one year old. According to VCUG findings, VUR grades were grouped as grade I-II-III low-grade VUR and IV-V high-grade VUR. The role of DRS in detecting VUR in both low and high-VUR-grade groups was evaluated. Results: A total of 56 patients (and 69 renal units), 23 girls (%41.1), and 33 boys (%68.9) were included in this study. The median value of the time elapsed between the DRS and VCUG examinations was nine days. According to VCUG, VUR was grade I in five renal units, grade II in 19 renal units, grade III in six renal units, grade IV in six renal units, and grade V in 33 renal units. DRS detected VUR in two of 30 renal units (%6.7) in the low VUR grade group. On the other hand, VUR was observed with DRS in 27 of 39 renal units (%69.2) in the high VUR grade group. Conclusions: Standardized DRS shows very low sensitivity in recognizing low-grade VUR, and its performance in detecting high-grade VUR is comparatively better. Raising awareness among clinicians that VUR can be observed with standardized DRS will benefit the patient in terms of early detection of accompanying VUR pathologies.